2017
DOI: 10.9778/cmajo.20170055
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing access to cervical and colorectal cancer screening for women in rural and remote northern Alberta: a pilot study

Abstract: Background: Women in rural and remote northern Alberta access breast cancer screening through a mobile mammogram program (Screen Test). The Enhanced Access to Cervical and Colorectal Cancer Screening (EACS) project was a 2-year pilot that aimed to integrate cervical and colorectal cancer screening with the Screen Test program. This study compares cervical and colorectal cancer screening uptake among women screened through the pilot (Screen Test-EACS) versus Screen Test.Methods: Screen Test-EACS was offered bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…The Ministry of Health in New Zealand 22 also suggested the use of community workers to distribute and collect kits for rural and remote communities, however, this may not be appropriate in rural and remote areas given the extensive distance between communities. Mema et al 45 suggested the integration of bowel screening services with existing mobile mammography. In this study, women who were already able to access mobile breast screening services also had the option of completing bowel and cervical screening, which was effective in increasing access and participation 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ministry of Health in New Zealand 22 also suggested the use of community workers to distribute and collect kits for rural and remote communities, however, this may not be appropriate in rural and remote areas given the extensive distance between communities. Mema et al 45 suggested the integration of bowel screening services with existing mobile mammography. In this study, women who were already able to access mobile breast screening services also had the option of completing bowel and cervical screening, which was effective in increasing access and participation 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, women who were already able to access mobile breast screening services also had the option of completing bowel and cervical screening, which was effective in increasing access and participation. 45 However, this strategy is associated with a high resource demand for trained health care workers, and logistical barriers such as transportation. Cancer Council Victoria 30 suggested health clinics offer flexible and out-of-hours appointments, transportation assistance, and group transportation for participation in screening services.…”
Section: Abilitymentioning
confidence: 99%
“…Mobile SCS are a feasible option to reach people who inject drugs in smaller communities for a number of reasons. Firstly, mobile health services have been effective in increasing participation in primary and secondary prevention services such as immunizations [14], cancer screening [15], and harm reduction [16]. Secondly, mobile injection services have been successfully piloted in Copenhagen, Demark; Berlin, Germany; and Barcelona, Spain [17].…”
Section: Discussionmentioning
confidence: 99%
“…The key of the success for a high adherence rate to counselling may be due to several factors: (i) by providing a more intimate, welcoming and less intimidating environment, the MHC put patients at the heart of the process, bringing healthcare into community spaces familiar to patients, allowing them to feel the sense of a more complete involvement and self-efficacy [11,43]; (ii) all services provided were completely free; (iii) opening hours were broader than primary care 'traditional' facilities; (iv) the counselling was offered on the same occasion of biometric screeningthe two services were provided in two adjacent wagons. Where practicable, it makes sense to integrate the provision of multiple services to enhance participation [48].…”
Section: Table 3 Distribution Of Newly Diagnosed and Uncontrolled Conmentioning
confidence: 99%